Talo as a Landscape Infrastructure; Examining the Nature of “Talo Wells” and Its Role in the Social Life of Laft Port City - Zahra Nazari (منظر)
Throughout history, the difficulties and constraints in the extraction of water resources have always made the supply and exploitation of water challenging for the people in the central and southern cities of Iran. However, such limitations have contributed to their water-related knowledge, insofar as the history of water engineering in Iran has witnessed the creation of masterpieces such as aqueducts and reservoirs. The city of Laft is not exempt from this rule due to its geographical location and special climatic conditions. Laft’s special conditions have created a phenomenon called “Talo wells”. The current research is an attempt to scrutinize the nature of the Talo complex as an ancient water infrastructure by analyzing written and oral sources related to the Laft area and Talo wells. It also relies on the knowledge of science related to the phenomenon of freshwater wells by examining its role in the social life of  Bandar Laft through the lens of landscape discipline. For this purpose, the location of Talo wells has been not viewed as just an engineering system for supplying water but rather a landscape phenomenon and infrastructure. This study employs a case study in which the data were collected from available literature, interviews, and field observations. Findings of the study show that “Talo” as the only water infrastructure in Bandar Laft, relies on a landscape infrastructure. Fresh water, as a vital and valuable element in the city, has contributed to the formation of the city-port of Laft and turned it into a civilized habitat. If, despite the special geographical location of Laft as the closest point of connection between Qeshm Island and the southern shores of the Persian Gulf and its effective role in creating settlement and business prosperity, without the discovery and management of freshwater resources in this port, the possibility of permanent settlement and the formation of an ancient city It did not exist and Laft became only a temporary resort and a connecting bridge between Qeshm Island and the coast of Hormozgan. In addition, Talo wells have a special place among the people of Laft because they provide access to limited and valuable sources of drinking water. The special and extraterrestrial position of water in this region has elevated the role of Talo wells from an urban water supply technique to a platform for the manifestation of philosophical concepts, sacred beliefs, interaction, and social participation of people in protecting water values.